2011
DOI: 10.1007/s00192-011-1552-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on tension-free vaginal tape obturator (TVT-O)

Abstract: The TVT-O is effective in treating female SUI with minimal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Abouassaly et al (2004) reported persisting suprapubic discomfort in 18 (7.5%) (18/241 patients). Rajendra et al (2011) after following up 419 patients for 3 years reported persistent pain in 15 patients (3.6%). Ross et al (2009) reported 199 patients, 105 of these had a TVT inserted and 94 patients had a TVT-O; they documented in the vaginal examination that the mesh was palpable in 68 (80%) in the TVT-O group and in 24 (27%) of the TVT group ( RR 0.22, CI 95% 0.13-0.37, P<.001); many women are also experiencing groin pain during vaginal palpation, 13 patients (15%) in the TVT-O group and 5 patients (6%) in the TVT group.…”
Section: Infectionmentioning
confidence: 98%
See 3 more Smart Citations
“…Abouassaly et al (2004) reported persisting suprapubic discomfort in 18 (7.5%) (18/241 patients). Rajendra et al (2011) after following up 419 patients for 3 years reported persistent pain in 15 patients (3.6%). Ross et al (2009) reported 199 patients, 105 of these had a TVT inserted and 94 patients had a TVT-O; they documented in the vaginal examination that the mesh was palpable in 68 (80%) in the TVT-O group and in 24 (27%) of the TVT group ( RR 0.22, CI 95% 0.13-0.37, P<.001); many women are also experiencing groin pain during vaginal palpation, 13 patients (15%) in the TVT-O group and 5 patients (6%) in the TVT group.…”
Section: Infectionmentioning
confidence: 98%
“…Barry et al (2011) in a multicentric, randomized trial comparing TVT-Monarc at 3 months follow up, report a bladder lesion in 7/140 patients with TVT and 0/140 patients with Monarc. Rajendra et al (2011) reported 419 patients with stress urinary incontinence at 3 years follow up, 2 patients (0.5%) with bladder perforation. Latthe et al (2010) in his systematic review of 4 articles, report that bladder lesions with the TOT procedure have an OR 0.11 (IC 95% 0.05-0.25) and TVTO has an OR of 0.15 (IC 95% 0.06-0.35).…”
Section: Bladder and Urethral Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, this operation with synthetic sling is considered the gold standard in the correction of SUI 5,6 . However, it is not without its adversities, such as extrusion, erosion, infection, and vessels, bowel or bladder perforations [7][8][9][10][11] . Taking into account all these factors and the clarification that it is necessary to the patient, an important part in the treatment choice, we decided to evaluate the implementation of an aponeurotic sling through a modified technique with direct visualization of the needles in patients with stress urinary incontinence.…”
mentioning
confidence: 99%